2018
DOI: 10.1186/s13014-018-1077-z
|View full text |Cite
|
Sign up to set email alerts
|

Quality assurance analysis of hippocampal avoidance in a melanoma whole brain radiotherapy randomized trial shows good compliance

Abstract: BackgroundMelanoma brain metastases (MBM) often cause morbidity and mortality for stage IV melanoma patients. An ongoing randomised phase III trial (NCT01503827 – WBRT-Mel) evaluates the role of adjuvant whole brain radiotherapy (WBRT) following local treatment of MBM. Hippocampal avoidance during WBRT (HA-WBRT) has shown memory and neurocognitive function (NCF) preservation in the RTOG-0933 phase II study. This study assessed the quality assurance of HA-WBRT within the WBRT-Mel trial according to RTOG-0933 st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…Hippocampal avoidant radiotherapy was shown using probabilistic sensitivity analysis as the preferred method in 77% of simulations. Other studies have confirmed the data quality from observational methods such as whole brain radiotherapy and the preferred hippocampal avoidant radiotherapy [ 35 , 36 ]. Aside from the cost considerations, additional research addressing improvable features of utilized observational methods could lead to better patient outcomes and conserve clinical resources.…”
Section: Resultsmentioning
confidence: 77%
See 1 more Smart Citation
“…Hippocampal avoidant radiotherapy was shown using probabilistic sensitivity analysis as the preferred method in 77% of simulations. Other studies have confirmed the data quality from observational methods such as whole brain radiotherapy and the preferred hippocampal avoidant radiotherapy [ 35 , 36 ]. Aside from the cost considerations, additional research addressing improvable features of utilized observational methods could lead to better patient outcomes and conserve clinical resources.…”
Section: Resultsmentioning
confidence: 77%
“…Manipulating WBRT dosage also showed no difference in effect on brain tumor size change or overall survivability, again indicating that WBRT is most likely not a favorable treatment approach [ 34 ]. Though most reporting on and the analysis of WBRT efficacy in MBM cases align with the aforementioned negative findings, a select few studies have seen WBRT improve palliation by prolonging both intracerebral and intracranial control [ 35 , 36 ]. Additionally, Janavicius and colleagues promoted WBRT as a means of preserving memory and neurocognitive function in MBM patients, which is in direct contention with earlier findings.…”
Section: Resultsmentioning
confidence: 90%
“…In a large phase III trial, Brown et al ( 101) reported that hippocampal avoidance-WBRT (HA-WBRT) can better protect cognitive function than traditional WBRT. Similarly, avoiding the hippocampus during WBRT has been shown to be closely related to improved neurocognitive function, avoidance of personality changes, and improved quality of life, as mentioned by V. Pareek (102). In addition, the results of phase III trial (NCT02360215) showed that the combined use of memantine after HA-WBRT resulted in a 23.3% deterioration of executive function after 4 months, with declines of 11.5% and 16.4% in learning and memory after 6 months (103).…”
Section: Whole Brain Radiotherapymentioning
confidence: 82%
“…This further refinement of the VMAT technique is known as the addition of a simultaneous integrated boost (SIB). 13 Extensive skin field cancerisation (ESFC) has been defined as that which has a clinically detectable surface area of over 50cm 2 . 14 In some anatomical sites (e.g.…”
Section: Introductionmentioning
confidence: 99%